1977
DOI: 10.1071/pp9770917
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Aleurone Layer. II. Fluorescence Microscopy of the Aleurone-Sub-Aleurone Junction With Emphasis on Possible β-1,3-Glucan Deposits in Barley

Abstract: The structural organization of the cell walls at the aleurone-sub-aleurone junction has been examined by fluorescence microscopy in ungerminated seeds of two varieties of Hordeum vulgare L. (cultivars Himalaya and Vanier). The sub-aleurone cell walls that are immediately adjacent to the aleurone layer are considerably thicker than the remainder of endosperm walls and contain extensive deposits of aniline blue-positive material. The latter was not significantly affected by periodate oxidation and was removed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…It thus belongs to the enzyme category EC 3.2.1.39 as opposed to EC 3.2.1.6. A potential substrate in barley and wheat for this enzyme is the aniline blue stainable deposits localized in the aleurone-subaleurone junction region (1,13). These deposits in barley have now been shown to be degradable by endo-1,3-13-giucanase purified in this study (MACGREGOR, BALLANCE and DUSHNICKY, manuscript in preparation) adding further evidence of the 1,3-13-glucan nature of these deposits.…”
Section: Introductionmentioning
confidence: 69%
“…It thus belongs to the enzyme category EC 3.2.1.39 as opposed to EC 3.2.1.6. A potential substrate in barley and wheat for this enzyme is the aniline blue stainable deposits localized in the aleurone-subaleurone junction region (1,13). These deposits in barley have now been shown to be degradable by endo-1,3-13-giucanase purified in this study (MACGREGOR, BALLANCE and DUSHNICKY, manuscript in preparation) adding further evidence of the 1,3-13-glucan nature of these deposits.…”
Section: Introductionmentioning
confidence: 69%
“…2A). Fulcher et al (1977) suggests that these deposits may be the primary substrate for high levels of b-(1,3)-glucanase activity present at the onset of germination. Both Fulcher et al (1977) and Bacic and Stone (1981a) recognized that variation in the pattern and size of callose deposits between barley varieties does not support a specific physiological function, although Fincher (1989) suggested that the variable patterns of callose distribution might have reflected a variable number of transient water stress events that caused plasmolysis and callose deposition during grain development.…”
Section: Discussionmentioning
confidence: 99%
“…Both Fulcher et al (1977) and Bacic and Stone (1981a) recognized that variation in the pattern and size of callose deposits between barley varieties does not support a specific physiological function, although Fincher (1989) suggested that the variable patterns of callose distribution might have reflected a variable number of transient water stress events that caused plasmolysis and callose deposition during grain development. The deposits may either influence the movement of substances during germination or they could simply be a remnant of developing walls (Fulcher et al, 1977). However, another possible explanation is that callose is being synthesized as a wound response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations